Divergent runoff impacts of permafrost and seasonally frozen ground at a large river basin of Tibetan Plateau during 1960–2019 - Lei Song; Lei Wang; Jing Zhou; Dongliang Luo; Xiuping Li (Environmental Research Letters, 2022)
Since the 20th century, due to global warming, permafrost areas have undergone significant changes. The degradation of permafrost has complicated water cycle processes. Taking the upper Yellow River basin (UYRB) as a demonstration, this study discusses the long-term (1960–2019) changes in frozen ground and their hydrological effects with a cryosphere-hydrology model, in particular a permafrost version of the water and energy budget-based distributed hydrological model. The permafrost at the UYRB, with thickening active layer and lengthening thawing duration, has degraded by 10.8%. The seasonally frozen ground has a more pronounced intra-annual regulation that replenishes surface runoff in the warm season, while the degradation of permafrost leads to a runoff increase. The occurrence of extreme events at the UYRB has gradually decreased with the degradation of frozen ground, but spring droughts and autumn floods become more serious. The results may help better understand the hydrological impacts of permafrost degradation in the Tibetan Plateau.